2022
DOI: 10.1038/s41564-022-01260-3
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin tilimycin from gut-resident Klebsiella promotes mutational evolution and antibiotic resistance in mice

Abstract: Klebsiella spp. that secrete the DNA-alkylating enterotoxin tilimycin colonize the human intestinal tract. Numbers of toxigenic bacteria increase during antibiotic use, and the resulting accumulation of tilimycin in the intestinal lumen damages the epithelium via genetic instability and apoptosis. Here we examine the impact of this genotoxin on the gut ecosystem. 16S rRNA sequencing of faecal samples from mice colonized with Klebsiella oxytoca strains and mechanistic analyses show that tilimycin is a pro-mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 72 publications
(106 reference statements)
1
19
0
Order By: Relevance
“…Multilocus sequence type 1 was assigned ( 14 ) (isolate 34) and cytotoxicity towards cultured human cells was assessed ( 15 ) (see strain 04/1O). Murine infection models confirmed in vivo toxin production by AHC-6 ( 16 , 17 ), identified the molecular targets of tilimycin and tilivalline, providing a mechanistic link to epithelial cell damage ( 7 , 16 ), and showed that the genotoxicity induced by tilimycin generates DNA lesions in enterocytes ( 16 ) and decreases microbial diversity while promoting the emergence of antibiotic resistance in the gut microbiome ( 18 ).…”
Section: Announcementmentioning
confidence: 98%
“…Multilocus sequence type 1 was assigned ( 14 ) (isolate 34) and cytotoxicity towards cultured human cells was assessed ( 15 ) (see strain 04/1O). Murine infection models confirmed in vivo toxin production by AHC-6 ( 16 , 17 ), identified the molecular targets of tilimycin and tilivalline, providing a mechanistic link to epithelial cell damage ( 7 , 16 ), and showed that the genotoxicity induced by tilimycin generates DNA lesions in enterocytes ( 16 ) and decreases microbial diversity while promoting the emergence of antibiotic resistance in the gut microbiome ( 18 ).…”
Section: Announcementmentioning
confidence: 98%
“…glucose). Support for this suggestion comes from a study done with in vitro systems inoculated with human faeces that showed TM (1–170 µM) exerted broad-spectrum activity against a range of Gram-positive and Gram-negative gut bacteria [ 79 ]. In mice TM caused reductions in the species richness and evenness of the murine gut microbiota, driving compositional changes [ 79 ].…”
Section: Virulence Of Klebsiella Spp and Cytotoxicitymentioning
confidence: 99%
“…Support for this suggestion comes from a study done with in vitro systems inoculated with human faeces that showed TM (1–170 µM) exerted broad-spectrum activity against a range of Gram-positive and Gram-negative gut bacteria [ 79 ]. In mice TM caused reductions in the species richness and evenness of the murine gut microbiota, driving compositional changes [ 79 ]. In addition, and of great concern with respect to the global and preterm burden of antimicrobial resistance in ESKAPE pathogens, TM directly contributed to de novo mutations in the genomes of Escherichia coli and K. pneumoniae strains that led to their resistance to rifampicin and nalidixic acid; a strain of Pseudomonas aeruginosa also acquired a resistance determinant associated with rifampicin upon exposure to TM [ 79 ].…”
Section: Virulence Of Klebsiella Spp and Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely recognized that the microbiome contributes to colonization resistance (CR) against diseasecausing pathogens 9,10 through various mechanisms. For instance, commensals can protect the host by utilizing growth-limiting carbon sources [5][6][7] , siderophores 11 , and oxygen consumption 8 or by producing bioactive molecules such as secondary bile acids 4 , short-chain fatty acids 12 and growth inhibitory toxins 13,14 . Diverse human-isolated commensal bacteria have also been described to enhance CR, either by preventing pathogen outgrowth or facilitating pathogen clearance.…”
Section: Introductionmentioning
confidence: 99%